Tradição e modernidade: des (entendimentos) no desenvolvimento de um software durante o processo de implantação da MPS.BR - Carla Floriana Martins (2017)
This work seeks to understand the contradictions related to the implementation of the MPS.Br model (Brazilian Software Improvement Model) deployed in the context of the development of a software. This study observed the impact of the MPS.br implementation in the way the company operated. Based on ethnographic-inspired field research, it was possible to perceive that substantial changes in the logics of production, results, relationships and communications between the communities of practices within the company. In particular, it was possible to note that the introduction of the MPS.Br contributed to the loss of the more artisanal, collaborative and communicative character that persisted in the company, transforming it towards the establishment of industrial and instrumental logics. In addition, after obtaining MPS.Br certification, the company's expectations to increase productivity were frustrated. Instead, software development became slower and more conflictive, compromising product quality and business viability. Based on this, the present study highlights the importance of collaborative forms of work and questions the use of rigid and traditional methodologies of software development such as MPS.Br. In addition, the research emphasizes that a better understanding of the performance of existing Communities of Practice in a given context, and the perception of the sociotechnical aspects of development of software can contribute to a perspective for Software Engineering more productive and less conflictual. In this way organizations can offer conditions that aim to facilitate collaborative work between teams and communities, obtaining, in this way, an improvement in the production of artifacts geared to the expansion of knowledge and conjunctures of organizations' transformations.